Changes [large type] - Nowak, Pamela (Thorndike Press, 2013)
In 1879, Omaha librarian Lise Dupree hides her part-Sioux heritage as she agrees to help research legal questions for a band of Ponca Indians. A quest for justice becomes a search for identity as she encounters ambitious district attorney Zach Spencer in a battle that will transform them both. In the process, they confront Lise's past, Zach's aspirations, the dangerous prejudice of an unstable Indian agent -- and their own smoldering attraction.